An odorant receptor from the common cutworm (Spodoptera litura) exclusively tuned to the important plant volatile cis‐3‐Hexenyl acetate. Issue 4 (16th May 2013) - Zhang, J.; Liu, C. C.; Yan, S. W.; Liu, Y.; Guo, M. B.; Dong, S. L.; Wang, G. R.
Abstract Olfaction plays an important role in insect behaviours. The odorant receptor (OR) repertoire, housed within the dendritic membrane of sensory neurons, is one of the primary determinants of odour recognition. ORs in moths could be classified into pheromone receptors (PRs) and non‐pheromone receptors (non‐PR ORs). Much research in the field of insect olfaction recently has been focused on PRs of the male moth, but few Lepidoptera studies have been done on the functional study of non‐PR ORs. In the present study, we identified and characterized four non‐PR ORs from Spodoptera litura (Lepidoptera: Noctuidae) antennae. The tissue expression pattern showed that the four ORs were mainly expressed in adult antennae and further in situ hybridization revealed SlituOR12 was expressed in both long and short sensilla trichodea and sensilla basiconica. A functional analysis of the four SlituORs was conducted in the heterologous expression system Xenopus oocytes. SlituOR12 was exclusively and sensitively tuned to cis‐3‐Hexenyl acetate and SlituOR19 slightly responded to 4′‐Ethylacetophenone; however, SlituOR44 and SlituOR51 did not respond to any chemicals tested in this study. It is proposed that SlituOR12 might partially account for some key behaviours of the female, such as detection of host location and oviposition site.